Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/v12020139
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Hepatitis E Virus (HEV) Culture and Its Application to Measurements of HEV Infectivity

Abstract: Hepatitis E virus (HEV) is a major concern in public health worldwide. Infections with HEV genotypes 3, 4, or 7 can lead to chronic hepatitis while genotype 1 infections can trigger severe hepatitis in pregnant women. Infections with all genotypes can worsen chronic liver diseases. As virions are lipid-associated in blood and naked in feces, efficient methods of propagating HEV clinical strains in vitro and evaluating the infectivity of both HEV forms are needed. We evaluated the spread of clinical strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…However, for decades, these cell culture systems did not allow replication of HEV at high levels. It is only recently that optimised cell models have been developed and high HEV viral loads detected in HepG2/C3A, A549, PLC/PRF/5 and Huh-7-Lunet BLR cells [24][25][26]. Increased viral replication has also been reported in hepatoma cells expressing HEV-1 ORF4 [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, for decades, these cell culture systems did not allow replication of HEV at high levels. It is only recently that optimised cell models have been developed and high HEV viral loads detected in HepG2/C3A, A549, PLC/PRF/5 and Huh-7-Lunet BLR cells [24][25][26]. Increased viral replication has also been reported in hepatoma cells expressing HEV-1 ORF4 [27].…”
Section: Introductionmentioning
confidence: 99%
“…About 2 h post-infection (hpi), the supernatant was removed, and the new DMEM containing 2% FBS was added, and the culture was maintained for 24 h. Then, 10-fold serially dilutions of the virus suspension were used to infect monolayer Vero cells in a 96-well plate for 72 h. Each dilution was tested with eight replicates in each experiment, and the wells were observed and scored for the presence or absence of cytopathic effect (CPE). The 50% tissue culture infectious dose (TCID 50 ) was calculated based on the Reed-Muench method (Capelli et al, 2020).…”
Section: Determination Of 50% Tissue Culture Infectious Dosementioning
confidence: 99%
“…For example, human hepatomaderived HepaRG and porcine hepatocyte-like PICM-19 cell lines have been shown to support HEV replication, and are useful for studying virus-host interactions and species barrier crossing, especially since HEV infection is a zoonosis in developed countries [61]. Capelli et al [62,63] showed that different HEV genotypes release more than 90% of the virus from the apical membrane after ORF1 encodes nonstructural proteins involved in viral replication [45,46]. A small multifunctional 13 kDa protein is expressed from ORF3, which facilitates HEV transport throughout the cell and acts as viroporin for the release of the infectious virus from the host cell [47,48].…”
Section: Hepatitis E Genome Organizationmentioning
confidence: 99%
“…For example, human hepatomaderived HepaRG and porcine hepatocyte-like PICM-19 cell lines have been shown to support HEV replication, and are useful for studying virus-host interactions and species barrier crossing, especially since HEV infection is a zoonosis in developed countries [61]. Capelli et al [62,63] showed that different HEV genotypes release more than 90% of the virus from the apical membrane after ), with a small multifunctional protein encoded by ORF3. Three different capsid proteins have been discovered in vitro during infection, i.e., gORF2-glycosylated, iORF2-infectious and cORF2-cleaved ORF2.…”
Section: Hepatitis E Genome Organizationmentioning
confidence: 99%
See 1 more Smart Citation